Effects of chess-based cognitive remediation training as therapy add-on in alcohol and tobacco use disorders: protocol of a randomised, controlled clinical fMRI trial. Issue 9 (6th September 2022) - Gerhardt, Sarah; Lex, Gereon; Holzammer, Jennifer; Karl, Damian; Wieland, Alfred; Schmitt, Roland; Recuero, Ainoa Jiménez; Montero, Juan Antonio; Weber, Tillmann; Vollstädt-Klein, Sabine
Abstract : Background: Alcohol and tobacco use disorders (AUD, TUD) are frequent, both worldwide and in the German population, and cognitive impairments are known to facilitate instances of relapse. Cognitive training has been proposed for enhancing cognitive functioning and possibly improving treatment outcome in mental disorders. However, these effects and underlying neurobiological mechanisms are not yet fully understood regarding AUD and TUD. Examining the effect of chess-based cognitive remediation training (CB-CRT) on neurobiological, neuropsychological and psychosocial aspects as well as treatment outcomes will provide insights into mechanisms underlying relapse and abstinence and might help to improve health behaviour in affected individuals if used as therapy add-on. Methods and analysis: N=96 individuals with either AUD (N=48) or TUD (N=48) between 18 and 65 years of age will participate in a randomised, controlled clinical functional MRI (fMRI) trial. Two control groups will receive treatment as usual, that is, AUD treatment in a clinic, TUD outpatient treatment. Two therapy add-on groups will receive a 6-week CB-CRT as a therapy add-on. FMRI tasks, neurocognitive tests will be administered before and afterwards. All individuals will be followed up on monthly for 3 months. Endpoints include alterations in neural activation and neuropsychological task performance, psychosocial functioning, and relapse or substance intake. Regarding fMRI analyses, a general linear model will be applied, and t-tests, full factorial models and regression analyses will be conducted on the second level. Behavioural and psychometric data will be analysed using t-tests, regression analyses, repeated measures and one-way analyses of variance. Ethics and dissemination: This study has been approved by the ethics committee of the medical faculty Mannheim of the University of Heidelberg (2017-647N-MA). The findings of this study will be presented at conferences and published in peer-reviewed journals. Trial registration: The study was registered in the Clinical Trials Register (trial identifier: NCT04057534 at clinicaltrials.gov).